Perancangan Data Warehouse Perguruan Tinggi untuk Kinerja Penelitian dan Pengabdian kepada Masyarakat - Agata Filiana; Andhika Galuh Prabawati; Maria Nila Anggia Rini; Gloria Virginia; Budi Susanto (Jurnal Teknik Informatika dan Sistem Informasi, 2020)
Accreditation is an evaluation to ensure the quality of a study program at higher education by completing two main documents for qualitative data and self-evaluation, namely Study Program Performance Report (LKPS) and Self Evaluation Report (LED) respectively. Data used for this process must be consistent and accurate, therefore a central repository is proposed. A data warehouse for the domain of Research and Community Service is built using the snowflake schema and a five-step approach methodology proposed for the educational data warehouse. The schema consisted of one fact table, ten dimension tables, and four bridge tables. Using a business intelligence tool, data from the data warehouse is queried and provided in a dashboard. The data warehouse successfully returned the qualitative data needed for LKPS. As for the evaluation data for LED, the data warehouse is able to fulfill seven out of ten requirements. The data for the remaining three are provided with a slightly different orientation to the requirement, this was due to the data source.